Respuesta :
32 - 4x + 36 = 92 - 6x - 48
-4x + 68 = 92 - 6x - 48
-4x + 68 = -6x + 44
-4x + 68 + 6x = 44
2x + 68 = 44
2x = 44 - 68
2x = -24
x = -24/2
Answer: x = -12 ✅
-4x + 68 = 92 - 6x - 48
-4x + 68 = -6x + 44
-4x + 68 + 6x = 44
2x + 68 = 44
2x = 44 - 68
2x = -24
x = -24/2
Answer: x = -12 ✅
the answer is 24/2 which is 12Step 1: Simplify both sides of the equation.4(8−x)+36=92−2(3x+24)(4)(8)+(4)(−x)+36=92+(−2)(3x)+(−2)(24)(Distribute)32+−4x+36=92+−6x+−48(−4x)+(32+36)=(−6x)+(92+−48)(Combine Like Terms)−4x+68=−6x+44−4x+68=−6x+44Step 2: Add 6x to both sides.−4x+68+6x=−6x+44+6x2x+68=44Step 3: Subtract 68 from both sides.2x+68−68=44−682x=−24Step 4: Divide both sides by 2.2x2=−242x=−12Answer:x=−12